PTU-183 Advice from a dietitian regarding the low fodmap diet broadly maintains nutrient intake and does not alter fibre intake. (22nd June 2015) - Staudacher, H; Ross, FS; Briscoe, ZM; Irving, PM; Whelan, K; Lomer, MC
Abstract : Introduction: Dietary restriction of certain fermentable carbohydrates (low FODMAP diet, LFD) is increasingly utilised for managing symptoms of irritable bowel syndrome (IBS). Exclusion diets carry a risk of nutritional inadequacy, and lower calcium intake has been reported during a LFD. Furthermore, it is important to understand whether the positive impact of the LFD is due to FODMAP restriction or an unintended dietary change (e.g. fibre intake). This single-blind randomised controlled trial aimed to compare nutrient intake in patients with IBS following LFD advice with baseline and a sham diet. Method: Adult patients with IBS referred to a secondary care dietetic service were screened for inclusion (n = 162). Suitable patients who were following their habitual diet (baseline) were randomised to blinded LFD advice or sham (placebo) dietary advice provided by a registered dietitian. The sham diet was designed to be equivalent in nutrients and FODMAP content compared with baseline intake. A 7-day diet record was completed and weight recorded at baseline and 4 weeks. Mean daily nutrient intakes were calculated from diet records (excluding supplements) entered into dietary composition software (Dietplan 6, Forestfield Software Ltd). Comparisons were made with dietary reference values (DRVs). Data was analysed using t-tests and McNemar tests. Results: A total of 95 patients completed the study (63 females, 66%) with 8 withdrawals and 1 lost to follow up (LFD n = 4, sham n = 5). Mean weight change was not different between groups (LFD -0.3 kg vs sham -0.4 kg, p = 0.738). There were no differences in mean energy and nutrient intakes, including calcium, between LFD and sham at baseline or follow up except vitamin B12 at follow up (LFD 6.3 µg/d vs sham 4.7 µg/d, p = 0.004). There was a significant reduction in mean iron intake in LFD from baseline (11.3 mg/d) to follow up (10.2 mg/d, p = 0.008), although proportion of LFD meeting the iron DRV did not differ (baseline 52% vs follow up 48%, p = 0.375). Proportion of LFD meeting the fibre DRV did not change (baseline 53% vs follow up 53%, p = 1.00). Proportion of LFD meeting the calcium DRV at baseline was higher (64%) than after LFD (47%, p = 0.039). Overall, mean LFD nutrient intakes were similar to data for the healthy population. Conclusion: More than half of patients following LFD advice did not meet DRVs for iron and calcium, although mean nutrient intakes were comparable to the healthy population. Energy and nutrient intake after LFD advice is not different to sham dietary advice, confirming that altered fibre intake is not responsible for its impact on IBS symptoms. Disclosure of interest: None Declared.